Facilitating Akt Clearance via Manipulation of Hsp70 Activity and Levels - Koren, John (American Society for Biochemistry and Molecular Biology, 2010)
Members of the 70-kDa heat shock family can control and manipulate a host of oncogenic client proteins. This role of Hsp70 in both the folding and degradation of these client proteins makes it a potential drug target for certain forms of cancer. The phenothiazine family of compounds, as well as the flavonoid myricetin, was recently shown to inhibit Hsp70-ATPase activity, whereas members of the dihydropyrimidine family stimulated ATPase function. Akt, a major survival kinase, was found to be under the regulation of Hsp70, and when the ATPase activity of Hsp70 was increased or decreased by these compounds, Akt levels were also increased or decreased. Also, increasing Hsp70 levels concurrent with inhibition of its ATPase function synergistically reduced Akt levels to a greater extent than either manipulation alone, providing new insights about client fate decisions. Akt reductions mediated by Hsp70 inhibitors were prevented when Hsp70 expression was silenced with small interfering RNA. Inhibiting Hsp70 ATPase function produced cytotoxic events only in breast cancer cell lines where Akt dysfunction was previously shown, suggesting therapeutic specificity depending on the Hsp70 client profile. Thus, increasing Hsp70 levels combined with inhibiting its ATPase function may serve to dramatically reduce Akt levels and facilitate cell death in certain types of cancer.